How Customer Perception Shape Buying Online Decision (Global Journal of Management and Business Research, 2014)
Consumers are playing an important responsibility in online shopping. When online retailers can identify the factors that can affect consumers' buying behaviour and the associations between these factors and type of online buyers, then they can further widen their marketing strategies to convert potential customers into active ones and at the same time remain the loyal customer as one of the asset of the business. The purpose of the paper will focus on some consumer perception toward buying online decision. It was discovered that overall website quality, commitment factor, customer service and purchase decision are key factors which influence consumers' perceptions, satisfaction and loyalty of online shopping. When customer unsatisfied with their purchases or increase number of acceptable brand, an individual will become less loyal and brand switching will be occur.
Keywords: online shopping; online purchase; electronic commerce; customer perception; customer behaviour; website characteristics; customer satisfaction; brand